Exploring Online Learning in University: Bridging the Gap between Practice and Perception - Nawal, Kherra (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
This study aims to evaluate the impact of implementing a hybrid training system in language teaching at Algerian universities during the Covid-19 pandemic. This research aims to understand students' perceptions and satisfaction and the effect of distance learning on their learning process. The methodology employed in this study is a mixed-methods approach, combining qualitative and quantitative techniques. A survey was conducted with 200 third-year students majoring in French Language and Literature, using online questionnaires and interviews to collect data on their experiences with the hybrid training system. Data analysis was performed using descriptive methods and content analysis. The study results indicate that 68% of students reported satisfaction with the hybrid training system, primarily due to the flexibility and variety of learning media. However, 23% of students complained about poor internet connection quality, and another 22% faced technical limitations such as a lack of devices. Overall, students appreciated the availability of instructors to answer questions online and provide prompt feedback. The implications of this study suggest that hybrid training has great potential to enhance the quality of language teaching in the digital era, although technical challenges still need to be addressed. The findings of this research can be used to develop more effective and adaptive training programs and to improve technical infrastructure to better support hybrid training in the future.